Table of Content - -, (Journal of Humanities & Social Sciences, 2025)
Table of Content:1. Soft Skills in Modern Education:  A New Approach for Effective Educational CommunicationDr. Mohamed Ouldhali2. Design a model to measure the effect of interior spaces on individuals with hyperactivity and attention deficit disorder (ADHD) to develop themMs. Nada Salem Al-Towairqi, Prof. Reem Farouq Al-Sabban3. Mail in the Caliphate of Al-Walid bin Abdul-Malik (86-96 AH/705-715 AD)Mr. Khalid Abdullah Alsaeed4. Spatial Analysis of Ambient Air Quality Variation in Dammam in Saudi ArabiaDr. Hessa Mohammed Aloatibi, Prof. Mohammed Ibrahim Al-Dagheiri5. Globalization and Its Impact on the Consumption Pattern of Female University Students: An Applied Study on University of Hail Female StudentsDr. Afaf Ali Al-Sayed, Lecturer \ Fathia Mohammed Al-Siddiq, Lecturer \ Lamia Saud Al-Aqili6. The Use of Geographic Information Systems (GIS) in Measuring the Accessibility to Educational Services in the Driouch province: A Geographical Approach for PlanningDr. El-Kallouchi Mohamed, Dr. Ismail Bouguelba
Keywords: Journal of Human and Social Sciences